Serum uromodulin and Roux-en-Y gastric bypass: improvement of a marker reflecting nephron mass - Scheurlen, Katharina; Billeter, Adrian; Kopf, Stefan; Nawroth, Peter Paul; Zeier, Martin; Müller, Beat P. (Surgery for obesity and related diseases, 2019)
Background - Early diagnosis of kidney disease in obese patients and in such patients with type 2 diabetes (T2D) can significantly improve treatment outcome. Serum uromodulin (sUMOD) may be a sensitive parameter for early detection of nephropathy. - Objectives - To analyze sUMOD and traditional markers of kidney function in a cohort study of patients with and without obesity or T2D undergoing metabolic surgery compared with blood donors. - Setting - University of Heidelberg, Germany. - Methods - Patients with obesity (body mass index >35 kg/m2) without T2D (n = 10) and T2D (n = 10) and patients with nonsevere obesity (body mass index, 25-35 kg/m2) and insulin-dependent T2D (n = 16) undergoing Roux-en-Y gastric bypass (RYGB) were enrolled. The control group consisted of 190 blood donors. sUMOD was compared with established renal markers. - Results - Using sUMOD, impaired kidney function at baseline was present in both groups with T2D and in none of the patients with obesity without T2D. This impairment was not detectable through traditional markers. Significant improvement of sUMOD was shown in patients with obesity and T2D 12 months postoperatively (from 130.0 ± 77.5 to 239.5 ± 179.0 ng/mL; P = .004) and in patients with nonsevere obesity and T2D 6 months after RYGB (from 140.6 ± 78.0 to 298.7 ± 154.0 ng/mL; P = .017). In patients with obesity without T2D, sUMOD remained stable (P = .375). - Conclusions - sUMOD may serve as a tissue-specific biomarker in incipient diabetic nephropathy. Improvement of sUMOD after RYGB seems to profoundly restore the structural integrity of nephrons in these patients at risk for diabetic nephropathy.
Gesehen am 26.11.2019